Atividade antimicrobiana de biocompostos produzidos por bactérias ácido láticas vis fermentação submersa usando subprodutos da agroindústria - Strack, Lariane (2021)
Consumers’ concern towards food has being increasing each year; consequently, there is an increased demand for products with less preservatives addition and that could provide healthier eating habits. Probiotics are bacteria that bring out several benefits to the organism of those who eat them; they have the ability to produce natural antimicrobial compounds, such as bacteriocins, that help reducing the use of preservatives and increasing shelf life of food products. Bacteriocins are proteins or a complex of proteins produced in the ribosome; they are capable of combating certain types of pathogens. The production of these components is expensive for industry; therefore, in this study the production of bacteriocins from probiotics is tested in low cost culture media. Lactic probiotic bacteria available in the microorganism bank of the Veterinary Medicine at Universidade de Passo Fundo – UPF were selected due to their ability to produce antimicrobial compounds that could inhibit contaminating fungi in cheeses. Bifidobacterium animalis subesp. Lactis, Lactobacillus lactis and Lactobacillus Reuteri were the microorganisms used. The process of submerged fermentation for producing antimicrobial compounds was studied taking notice the influence of factors such as Sucrose, NaCl and pH in bacteriocins creation, using whey as a substratum. The fermentation happened in a two steps process; the first was identifying the best cultivation conditions for the production of extracts with antimicrobial potential in relation to the variation of the tested factors. The second one was to validate the best time of fermentation. As the object of analysis, 10 samples of country cheese produced in agro-industries from the north of Rio Grande do Sul state and western region of Santa Catarina state were collected in a way to isolate and identify contaminating fungi. From the results obtained, it was possible to realize that pH and NaCl concentration were important factors to the results in relation to the pathogenic microorganisms studied (Penicilliums pp. and Staphylococcus aureus). It was possible to realize, too, that cultivation conditions varied from tests with bacteria and fungi. The antibacterial potential was more intense in extracts with less (NaCl) concentration, while anti fungi potential was higher when (NaCl) concentration was greater. The results of this study may contribute for future research, once it points the anti fungi potential of Bifidobacterium animalis subesp. lactis and Lactobacillus lactis. in relation to the fungi Penicillium spp.